Tools and Approaches for Studying Microglia In vivo - Eme-Scolan, Elisa; Dando, Samantha J. (Frontiers in Immunology, 2020)
Microglia are specialized resident macrophages of the central nervous system (CNS) that have important functions during neurodevelopment, homeostasis and disease. This mini-review provides an overview of the current tools and approaches for studying microglia in vivo. We focus on tools for labelling microglia, highlighting the advantages and limitations of microglia markers/antibodies and reporter mice. We also discuss techniques for imaging microglia in situ, including in vivo live imaging of brain and retinal microglia. Finally, we review microglia depletion approaches and their use to investigate microglial function in CNS homeostasis and disease.